ANALISA KESALAHAN DALAM MENGGUNAKAN TENSES OLEH MAHASISWA MANAJEMEN INFORMASI KESEHATAN DI INSTITUT KESEHATAN DELI HUSADA DELI TUA TAHUN 2018 - Herawati Br Bukit; Dila Fitria (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2019)
We can find the term Error Analysis in language. These errors could be valuable sources forteaching. We as learner must be able to know about tenses so that it can make miscommunicationone another. Students often confused about tenses. They assume tense as a significant burden.The error term is the fact that students always make mistakes in using tenses, and it is a problemthat the researcher finds. The researcher wants to find out both the students’ progress and everystudent’s level in understanding tenses. The method of this research used quantitative method.Kinds of errors made by first-grade students of Health Information Management in using tensesare omission 50% (omission of pure present tense 50%). The percentage errors of using tensesare simple present 50%, pure past 35%, and simple future tense 15%. The students should payattention seriously in learning tenses because tenses are part of grammar.